Performance and behavior of storey school bulding reinforced concrete structure under Acheh and Bukit Tinggi earthquake loading - Nurnajat Nadira, Abdul Rahman (2017)
A lot of building in Malaysia is not design according to code that specifies seismic provision since Malaysia is located away from active seismic fault zones. Unfortunately, several tremors comes from neighbouring country especially Indonesia have expose local existing structure to a risk which may not withstand the earthquake load. This research is done to study the seismic behaviour of four storey reinforced concrete building due to Aceh and Bukit TInggi earthquake. Since reinforce concrete structures are widely used in this country, the behaviour of this types of structure is observed to model and analyses the reinforced concrete structure subjected to different earthquake loads using SAP 2000 program and also to determine the best mode shape of free vibration analysis. Besides that, this research also to study the behaviour of four storey RC structure that is subjected to different earthquake loading and to determine the performance of RC structure during earthquake force. All the data of earthquake load were taken from Malaysia Meteorological Department (MMD). Eurocode 8 that considering seismic provision were used for response spectrum analysis. From the analysis, the vulnerability of reinforced concrete structure and dynamic characteristic can be obtain and used for design a safer structure.